Pursuing green growth in technology firms through the connections between environmental innovation and sustainable business performance: Does service capability matter? - Fernando, Yudi; Jabbour, Charbel Jose Chiappetta; Wah, Wen Xin (Elsevier Ltd, 2019)
In response to greater environmental awareness among stakeholders, companies have become increasingly interested in practices such as eco-innovation. Despite the expanding literature on eco-innovation, scholars have so far paid little attention to the study of eco-innovation and its impact on business sustainability, particularly considering the mediating effect of service innovation capability. To fill this research gap, this study extends the concepts of green business by investigating an original conceptual framework, which proposes that the capacity for service innovation has a mediating effect on the relationship between sustainable organizational performance and environmental innovation. This conceptual framework is subjected to empirical testing, implemented through a survey involving 95 Malaysian firms which use green technology. Data is collected through both postal and online questionnaires and analyzed through structural equation modeling using partial least squares. Respondents for this paper were identified using the directories of MyHijau (2013) and the Malaysia External Trade Development Corporation, 2014. The results suggest that: (1) eco-innovations unlock better sustainable performance; (2) service innovation capability has a partially significant positive mediating effect; (3) service innovation capability ultimately benefits companies by allowing them to differentiate through an emphasis on value creation; (4) service capability can also act as a business strategy to create barriers to new entry by competitors. Thus, eco-innovation and service innovation capability tend to represent significant intangible resources and enable an organization to achieve long-term objectives, competitive advantage and business sustainability. To date, this is the first study relating eco-innovation, service innovation capability and sustainability performance in the Malaysian corporate context and using a specific sample of companies that make use of green technologies.